2021
DOI: 10.1007/s00432-021-03811-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo-like leukoderma as an indicator of clinical response to immune checkpoint inhibitors in late-stage melanoma patients

Abstract: Purpose. Although development of immune checkpoint inhibitors has revolutionized the treatment of metastatic melanoma, more than a half of treated patients experience disease progression during therapy. Cases of spontaneous vitiligo-like leukoderma have been described in melanoma patients and have been associated with a favorable outcome. This vitiligo-like leukoderma can also appear in melanoma patients undergoing immune therapies such as immune checkpoint inhibitors. However, no consensus exists about the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Furthermore, it has been demonstrated that specific types of IRAEs exhibit a more profound correlation to treatment effectiveness and the type of these IRAEs differ across various cancer types. For example, vitiligo has been linked to treatment response in melanoma patients and thyroid dysfunction in NSCLC and renal cell carcinoma patients (24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that specific types of IRAEs exhibit a more profound correlation to treatment effectiveness and the type of these IRAEs differ across various cancer types. For example, vitiligo has been linked to treatment response in melanoma patients and thyroid dysfunction in NSCLC and renal cell carcinoma patients (24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…These biomarkers of response to therapy would permit to better address melanoma patients towards the most efficacious treatments. In this regard, the intent of our work was the identification of predictive and/or early biomarkers of response to anti-PD-1 antibodies, taking advantages of previously identified biomarkers of an active vitiligo disease, since vitiligo-like leukoderma represents an irAE that often occurs during CPI therapy in melanoma patients and correlates with a positive outcome 48 . In fact, we confirmed also in our melanoma patient subset the association between development of leukoderma and a favorable clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that leukoderma development has been described in melanoma patients receiving CPI immunotherapy and it has been associated with a positive response to therapy [25][26][27][28][29]48 , we hypothesized that immunological mechanisms like those activated in vitiligo pathogenesis could be also triggered in melanoma patients responding to CPI therapy. If this would be the case, the same biomarkers that identify vitiligo active phase could also represent biomarkers of patient response to CPI therapy.…”
mentioning
confidence: 99%
“…In specific conditions, autoimmune diseases have been linked to improved immunosurveillance, as exemplified for autoimmune thyroiditis and thyroid cancer, 9 , 10 vitiligo and melanoma 11 , 12 or non-cirrhotic primary biliary cholangitis and cholangiocarcinoma. 13 Moreover, in preclinical models, vaccination with normal epithelial cells from the intestine or the mammary gland can induce protective immune responses against colon and breast cancer, respectively, underscoring the possibility that immune responses against (by definition) non-mutated self-antigens can participate to cancer immunosurveillance.…”
mentioning
confidence: 99%